Оценка количества воды, связанной с оксиэтилированными производными глицерина - Животова, Е.Н.; Духопельников, Е.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Hydration number of molecules of oxyethylated glycerol (OEG) of polymerization degree n = 5, 25, and 30 has been determined by infrared spectroscopy. According to the experimental results, an OEG n = 5 molecule is able to bind about 20 water molecules, an OEG n = 25 molecule is able to bind about 75 water molecules, and an OEG n = 30 molecule is able to bind about 90 water molecules. Tendency of OEG molecules to form hydrogen bonds with water molecules can explain the sufficiently high cryoprotective activity of these compounds.